1997
DOI: 10.1007/s003740050337
|View full text |Cite
|
Sign up to set email alerts
|

Water- and pyrophosphate-extractable humic substances fractions as a source of iron for Fe-deficient cucumber plants

Abstract: The capacity of Fe-deficient cucumber plants to utilise water-extractable and pyrophosphate-extractable humic substances as a source of Fe was investigated. Plants were grown for 13 days in nutrient solution in the presence or absence of Fe and during the last 7 days water-extractable and pyrophosphate-extractable humic substances were added to the solution at a final concentration of 5 mu g organic C ml(-1). The water-extractable humic fraction did not significantly modify leaf area and dry matter accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 18 publications
5
62
0
6
Order By: Relevance
“…An analogous process has been described for flavonoids and citrate released by roots of white lupin, which, solubilizing Fe from an insoluble Fe phosphate, favored indirectly the mobilization and the availability of phosphate (Shaw et al 2006;Tomasi et al 2008). With respect to Fe, it has been demonstrated that the Fe-mobilization capacity of these organic ligands (Cesco et al 2000(Cesco et al , 2010 and the contribution of their Fe complexes in the acquisition process of the micronutrient by plants (Cesco et al 2002(Cesco et al , 2006Pinton et al 1999;Tomasi et al 2009a, b) could be quite different among the complexes. In the mobilization process, MS s can act alone or in combination with simple carboxylic acids and organic reducing agents of different origin; in this combined form, an additive effect with an enhanced extent of Fe dissolution from minerals has been observed (Dhungana et al 2007;Dehner et al 2010).…”
Section: Fe Complexation Processesmentioning
confidence: 79%
See 2 more Smart Citations
“…An analogous process has been described for flavonoids and citrate released by roots of white lupin, which, solubilizing Fe from an insoluble Fe phosphate, favored indirectly the mobilization and the availability of phosphate (Shaw et al 2006;Tomasi et al 2008). With respect to Fe, it has been demonstrated that the Fe-mobilization capacity of these organic ligands (Cesco et al 2000(Cesco et al , 2010 and the contribution of their Fe complexes in the acquisition process of the micronutrient by plants (Cesco et al 2002(Cesco et al , 2006Pinton et al 1999;Tomasi et al 2009a, b) could be quite different among the complexes. In the mobilization process, MS s can act alone or in combination with simple carboxylic acids and organic reducing agents of different origin; in this combined form, an additive effect with an enhanced extent of Fe dissolution from minerals has been observed (Dhungana et al 2007;Dehner et al 2010).…”
Section: Fe Complexation Processesmentioning
confidence: 79%
“…A link between organic acid excretion and proton extrusion by roots of white lupin has been clearly demonstrated (Tomasi et al 2009a, b). Plasma membrane H + -ATPase activity of roots, mainly involved in the proton extrusion coupled with the release of citrate previously described, is known also for being stimulated by soil HS (Pinton et al 1997a). In soils with low Fe availability, the occurrence of organic acid (citric, malic, and oxalic) also contributes to pH decrease when their exudation is coupled with proton efflux; the concentration in the rizodeposition varies among plant species and depends on soil pH (Hinsinger et al 2003).…”
Section: Soil Ph: Acidification and Alkalinization Of The Soil Enviromentioning
confidence: 94%
See 1 more Smart Citation
“…The corrective effect was attributed to complexation of Fe by HS in the organic materials. The ability of Fe-deficient plants to use Fe bound by water extractable (from peat) HS fraction was investigated by Pinton et al (1999). Studies conducted by our group have shown (Amichai 2001) that various fractions of DaM extracted, isolated and purified from compost bind Fe, maintain it in NS and provide this essential element to plants.…”
mentioning
confidence: 99%
“…Previously, an aqueous extract of sphagnum peat was found to be an iron-rich substrate due to its content of water-soluble humic substances, which may explain the downregulation of proteins involved in iron transport in cells grown in the peat extract (Pinton et al, 1998). Cytryn et al (2007) reported on the genome-wide transcriptional analysis of B. japonicum response to desiccation stress.…”
Section: Discussionmentioning
confidence: 99%